2022
DOI: 10.3389/fpsyg.2022.792642
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits, Technology-Related Teaching Skills, and Coping Mechanisms as Antecedents of Teachers’ Job-Related Affective Well-Being and Burnout in Compulsory and Higher Education Online Teaching Settings

Abstract: Teachers’ job-related well-being has been affected by the sudden shift to emergency remote online teaching due to the COVID-19 pandemic which has totally reshaped the task performance. Therefore, this study attempts to enlighten the possible reasons for the deterioration in teachers’ job-related well-being and proposes an integrated application of three models of prediction for job-related affective well-being and burnout as teachers’ indicators for the well-being in online teaching settings. The first model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 138 publications
1
5
0
Order By: Relevance
“…This factor leads us to reflect on the importance of coping strategies that might improve one’s response to an emergency. Indeed, several reports have shown that coping strategies mediate between burnout and well-being in the workplace [ 89 , 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This factor leads us to reflect on the importance of coping strategies that might improve one’s response to an emergency. Indeed, several reports have shown that coping strategies mediate between burnout and well-being in the workplace [ 89 , 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reveal how important coping strategies are for school administrators and teacher trainers, helping to increase educators’ understanding of work-related stress and its connection with work manageability [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, the findings revealed positive relations between teachers’ previous ICT usage and perceived stress and exhaustion. In another study, Stan (2022) examined the additional value of TPACK in explaining the relation between job burnout and job-related affective well-being over and above personality traits. The result showed that teachers’ TPACK was negatively related to job burnout and positively related to well-being.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Considering the central role of ICTs in the unprecedented change of face-to-face instruction to online teaching, some technology-related variables including attitudes toward change ( Daumiller et al, 2021 ), previous ICT training ( Stang-Rabrig et al, 2022 ), and Internet/device access and connection quality ( Kamal and Illiyan, 2021 ) have been sparingly examined to shed more light on their contribution to the status of teachers’ mental health during the pandemic. In this framework, very few researchers have shown interest in the interdependence of teachers’ ICT skills and knowledge, job burnout, and coping mechanisms (e.g., Stan, 2022 ), in spite of the fact that technological and pedagogical content knowledge (TPACK) has been documented to be related to teachers’ technostress in pre-pandemic studies ( Kay, 2008 ; Joo et al, 2016 ). To address this lacuna in research, the current study assumes a key role for TPACK as one essential resource that can assist teachers in adopting coping strategies to manage their job burnout during the pandemic.…”
Section: Introductionmentioning
confidence: 99%